Cucumber RDR1s and cucumber mosaic virus suppressor protein 2b association directs host defence in cucumber plants. (6th August 2021) - Kumari, Reenu; Kumar, Surender; Leibman, Diana; Abebie, Bekele; Shnaider, Yulia; Ding, Shou‐Wei; Gal‐On, Amit
Abstract: RNA‐dependent RNA polymerases (RDRs) regulate important aspects of plant development and resistance to pathogens. The role of RDRs in virus resistance has been demonstrated using siRNA signal amplification and through the methylation of viral genomes. Cucumber ( Cucumis sativus ) has four RDR1 genes that are differentially induced during virus infection: CsRDR1a, CsRDR1b, and duplicated CsRDR1c1 / c2 . The mode of action of CsRDR1s during viral infection is unknown. Transient expression of the cucumber mosaic virus (CMV)‐2b protein (the viral suppressor of RNA silencing) in cucumber protoplasts induced the expression of CsRDR1c, but not of CsRDR1a/1b . Results from the yeast two‐hybrid system showed that CsRDR1 proteins interacted with CMV‐2b and this was confirmed by bimolecular fluorescence complementation assays. In protoplasts, CsRDR1s localized in the cytoplasm as punctate spots. Colocalization experiments revealed that CsRDR1s and CMV‐2b were uniformly dispersed throughout the cytoplasm, suggesting that CsRDR1s are redistributed as a result of interactions. Transient overexpression of individual CsRDR1a/1b genes in protoplasts reduced CMV accumulation, indicating their antiviral role. However, overexpression of CsRDR1c in protoplasts resulted in relatively higher accumulation of CMV and CMVΔ2b. In single cells, CsRDR1c enhances viral replication, leading to CMV accumulation and blocking secondary siRNA amplification of CsRDR1c by CMV‐2b protein. This suggests that CMV‐2b acts as both a transcription factor that induces CsRDR1c (controlling virus accumulation) and a suppressor of CsRDR1c activity. Abstract : Cucumber mosaic virus 2b interferes with functioning of cucumber RDR1s (CsRDR1a/CsRDR1b/CsRDR1c) by direct interaction and induces transcription of CsRDR1c to exponential‐fold to control virus accumulation.